Induction Motor Dynamics Regimes: A Comprehensive Study of Mathematical Models and Validation - Marina Konuhova (Applied Sciences)
This study investigates the dynamic behavior of induction motors (IMs) by developing and validating four distinct mathematical models designed for transient and starting regimes. These models, expressed in α,β and d,q coordinate systems, analyze rotational frequency, electromagnetic torque, and current profiles with varying levels of complexity, including current-based, flux linkage-based, and rotor winding electromagnetic time constant approaches. Implemented in Fortran, the models address the limitations of predefined tools like MATLAB/Simulink, offering enhanced precision, flexibility, and suitability for non-standard scenarios. Validation against experimental data from a 3 kW induction motor confirms the models’ accuracy, with consistent results across approaches. Notably, the flux linkage models excel in capturing intricate transient phenomena, while current-based models simplify integration with power system studies. These findings provide a robust framework for analyzing IM performance under diverse conditions such as voltage unbalance and rundown scenarios, enabling the optimization of motor operations in energy-intensive industries.